(untitled) (Indian Journal of Public Health Research & Development, 2020)
Varicella is a contagious viral disease which is caused by Varicella Zoster. Nosocomial Varicella is costly for healthcare settings increasing absenteeism and hampering quality patient care. Human are the only known susceptible host for this viral illness. The disease is usually acute and self-limiting but occasionally can lead to complications such as encephalitis, pneumonia, and secondary bacterial infections. Once believed to be the infection of pediatric age group now gripping mostly adults in a severe manner in health care setting. The previous vaccination and primary episode of infection are not found to be protective. In India, >30% of persons >15 years of age are susceptible for this infection. Reports have suggested the airborne transmission plays a key role in transmission of Varicella Zoster in health care settings In health care setting the close contact between subclinical cases and susceptible individuals favors the rapid spread of the disease. Areas like Intensive Care Units (ICUs) are the most focal point of spread as immunity of admitted individuals are mostly compromised. The closed cubicles and chambers of the resident and working nursing officers in hospital setting act as a point of focus for the disease spread. Strict isolation words and quarantine procedures to be followed at institutional level for limiting viral dissemination. Knowledge building activities like Hand washing, Barrier nursing and mask use to be promoted among all health care staffs. Institutional policy to be made in order to control any viral outbreaks.